Relações da gestão escolar com resultados de rendimento aferidos pela avaliação em larga escala em colégios do estado do Paraná (2017 a 2021) - Soligo, Marinez Gasparin (2025)
The contexto of educational policies brings numerous debates to the Brazilian education scenario. Among these are school management and large-scale assessments. Both topics are amplified within the contexto of state reform and neoliberalismo. The research presentes as a problem the extent to which the characterisitics of manegement and influenc school performace as measured by the SAEB exam. The general objective was to analyze how the contextual características of manegement and manegers impact school performace as measeured by the SAEB exam. Adopting a mixed-methods approach, combining statistical modeling, literature review, and a comparative framework, the research draws on date from INEP databases, specifically contextual questionnaires completed by principals from sixty eight public schools located in municipalities of Paraná with fewer than 5,000 inhabitants. All selected schools had only one ninth-grade class in the final years of elementary education and publicly available IDEB results for the 2017, 2019, and 2021 cycles. The overarching objective was to examine the extent to which contextual factors related to school management influence student achievement in SAEB. The qualitative component involved in-depth case analysis and a critical discussion of the research subject. The initial hypothesis posited that participatory and democratic management practices positively affect academic performance. Findings indicate a significant association between contextual variables and student outcomes, supporting the initial premise. However, challenges in accessing, processing, and interpreting certain datasets limited the scope of the analysis, due to changes in the format and number of questions and information being masked for date protection. Results suggest that management stability, prior teaching experience, and exclusive dedication to the school board are generally linked to higher scores. Notably, permanence in office, more than total years of experience, appears to foster the consolidation of effective pedagogical practices and institutional strengthening. The study concludes that democratic, participatory school management committed to pedagogical processes is a key factor in enhancing learning outcomes, especially when supported by shared governance, administrative stability, and coordinated actions between schools and their communities.